Componente lento do V̇O2 em crianças durante exercício pesado de corrida: Análise com base em diferentes modelos matemáticos - Machado, Fabiana Andrade [UNESP]; Guglielmo, Luiz Guilherme Antonacci [UNESP]; Greco, Camila Coelho [UNESP]; Denadai, Benedito Sérgio [UNESP] (FapUNIFESP (SciELO), 2006)
The purpose of this study was to identify and quantify the magnitude of the slow component of VO2 (SC) in children during running exercise, performed at heavy intensity domain (75%Δ), using two different mathematical models: a) three-exponential model and; b) ΔVO2 6-3 min. Eight healthy male children (11.92 ± 0.63 years; 44.06 ± 13.01 kg; 146.63 ± 7.25 cm; and sexual maturity levels 1 and 2), not trained, performed in different days the following tests: 1) incremental running treadmill test to determine the peak oxygen uptake (VO2peak) and the lactate threshold (LT); and 2) two transitions from baseline to 75%Δ [75%Δ = LT + 0.75 x (VO2 peak - LT)] for six minutes on treadmill. The SC was determined by two models: a) three-exponential model (Exp3); and b) the VO2 difference between the sixth and the third exercise minute (ΔVO2 6-3min). The SC was expressed as the absolute (ml/min) and percent contribution (%) to the total change in VO 2. The SC values determined by model Exp3 (129.69 ± 75.71 ml/min and 8.4 ± 2.92%) and ΔVO2 6-3 min (68.69 ± 102.54 ml/min and 3.6 ± 7.34%) were significantly different. So, the SC values in children during running exercise performed at heavy intensity domain (75%Δ) are dependent of the analysis model (Exp3 x ΔVO2 6-3 min).
Slow component of V̇O2 in children during running exercise performed at heavy intensity domain: Analysis with different mathematical models
Keywords: Children; Heavy exercise; Running; Slow component